Histone modification and chromatin remodeling in plant response to pathogens - Kang, Huijia; Fan, Tianyi; Wu, Jiabing; Zhu, Yan; Shen, Wen-Hui (Frontiers in Plant Science, 2022)
As sessile organisms, plants are constantly exposed to changing environments frequently under diverse stresses. Biotic stresses, including virus, bacterial and fungal infections, can severely impede plant growth and development, causing important yield loss and thus challenging food/feed security worldwide. During evolution, plants have adapted complex systems, including coordinated global gene expression networks, to defend against pathogen attacks. In recent years, growing evidences indicate that pathogen infections can trigger local and global epigenetic changes that reprogram the transcription of plant defense genes, which in turn helps plants to fight against pathogens. Here, we summarize up plant defense pathways and epigenetic mechanisms and we review in depth current knowledges about histone modifications and chromatin remodeling factors found in the epigenetic regulation of plant response to biotic stresses. It is anticipated that epigenetic mechanisms may be explorable in the design of tools to generate stress-resistant plant varities.